COVID-19 impact on labour market in EU countries – differences in men and women employment rate tendencies - Markowska, Małgorzata; Strahl, Danuta (Technological and Economic Development of Economy, 2024)
This paper aims to identify the differences in the employment rate dynamics in economy sections, considering gender, in the European Union countries in 2020, compared to the 2008–2019 period. Two methods were used. The first method compares forecasts from models describing employment changes in the pre-pandemic periods with information concerning the actual employment rate in 2020, using three indices measuring the significance of the observed discrepancies. The second method uses dynamic cluster analysis for the 2008–2020 period, and evaluates the changes in composition of groups that occured in 2020. The proposed methods were applied separately to the data concerning the employment of females and males (employment rates) in the EU countries, always divided into economy sections and section groups (A, B-E, F, G-I, J, K, L, M and N, O-Q, R). The application of the “Triple 2 Rule” helped to identify the changes in the previous employment trends (“Interventions”). The evaluation of changes in the dynamics of the employment rate in total and in section groups and according to gender in the EU countries in 2020 – compared to the forecasts from the 2013–2019 trends – revealed that the EU labour market responded differently to the COVID-19 pandemic situation. First published online 14 March 2024